Exploring the efficacy of using hypertonic saline for nebulizing treatment in children with bronchiolitis: a meta-analysis of randomized controlled trials - Hsieh, Chia-Wen (BMC Pediatr, 2020)
BACKGROUND: Inhaled hypertonic saline (HS) has shown benefit in decreasing airway edema in acute bronchiolitis which is the most common lower respiratory infection resulting in dyspnea among infants under 2 years old. The aim of this systematic review and meta-analysis was to evaluate the efficacy and safety of HS in the implementation of treatment with nebulized HS among children with bronchiolitis. METHODS: A systematic literature search was conducted using Cochrane Library, PubMed, EMBASE and Airiti Library (Chinese Database) for randomized controlled trials from inception to July 2019. We calculated pooled risk ratios (RR), mean difference (MD) and 95% CI using RevMan 5.3 for meta-analysis. RESULTS: There were 4186 children from 32 publications included. Compared to the control group, the HS group exhibited significant reduction of severity of respiratory distress, included studies used the Clinical Severity Score (n = 8; MD, − 0.71; 95% CI, − 1.15 to − 0.27; I(2) = 73%) and full stop after Respiratory Distress Assessment Instrument (n = 5; MD, − 0.60; 95% CI, − 0.95 to − 0.26; I(2) = 0%) for evaluation respectively. Further, the HS group decreased the length of hospital stay 0.54 days (n = 20; MD, − 0.54; 95% CI, − 0.86 to − 0.23; I(2) = 81%). CONCLUSIONS: We conclude that nebulization with 3% saline solution is effective in decreasing the length of hospital stay and the severity of symptoms as compared with 0.9% saline solution among children with acute bronchiolitis. Further rigorous randomized controlled trials with large sample size are needed.